Edukasi Pentingnya Konsumsi Buah dan Sayur Menggunakan Media Leaflet di Posyandu Dahlia Kelurahan Anggalomelai Kecamatan Abeli Kota Kendari Tahun 2024 - Hartati Bahar; Dhea Sakila; Nur Amal Sasmita; Rakhmatullah Syawal; Yeni Yeni; Wa Ode Rizki Fatmala; Devi Savitri Effendy; Febriana Muchtar; Hariati Lestari (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
Between 2015 and 2020, the intake of fruits and vegetables in Indonesian people was less than 400 grams/day, which is the recommended nutritional adequacy level (RDA). The purpose of this education is to improve the knowledge of mothers at the Dahlia Posyandu about the importance of consuming fruits and vegetables. This education uses a lecture method with leaflet media. The selection of leaflet media is assumed to be easy for mothers to carry at the Posyandu. The results of the education showed that there was a significant difference between the pre and post tests which were tested using the Paired T-test statistical test, with a p value = 0.000, <0.05 meaning that there was a significant difference in knowledge before and after the intervention was given. It was concluded that education was successful in changing mothers' knowledge about fruit and vegetable consumption at the Dahlia Posyandu, Abeli District, Kendari City.